Respuesta :
Answer:
2x - 3y = - 12
Step-by-step explanation:
The equation of a line in standard form is
Ax + By = C ( A is a positive integer and B, C are integers )
Given
y = [tex]\frac{2}{3}[/tex] x + 4
Multiply through by 3
3y = 2x + 12 ( subtract 3y from both sides )
0 = 2x - 3y + 12 ( subtract 12 from both sides )
- 12 = 2x - 3y ⇒ 2x - 3y = - 12 ← in standard form
The answer in standard form can be written 2x - 3y= -12
The first step is to make y the subject of formula
2x - 3y= - 12
y= 2/3x + 12/3
y= 2/3x + 4
multiply through by 3
y(3)= 2/3(3) + 4(3)
3y= 2x + 12
subtract 3 from both sides of the equation
3y-3= 2x+12+3y
0= 2x+3y+12
collect the like terms
0-12= 2x+3y
-12= 2x+3y
2x+3y= -12
Therefore the standard form of the equation is
2x+3y= -12
Please see the link below for more information
https://brainly.com/question/11549642?referrer=searchResults